1976
DOI: 10.1093/infdis/133.supplement_2.a114
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical and Laboratory Evaluation of the Prophylactic Capacity of Ribavirin, Amantadine Hydrochloride, and Placebo in Induced Human Influenza Type A

Abstract: The comparative prophylactic effectiveness of oral treatment with ribavirin (1-beta-D-ribofuranosyl-1,2,4,triazole-3-carboxamide; virazole) and amantadine hydrochloride against artificially induced infection with influenza A virus was evaluated in 29 seronegative men who received ribavirin capsules (200 mg) three times daily, placebo capsules three times daily, or amantadine capsules (100 mg) twice daily. Medication was started two days before the inoculation of 2 X 10(4) 50% tissue culture infective doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 6 publications
0
29
0
2
Order By: Relevance
“…Furthermore, in a randomized, controlled study, 11 students infected with influenza B virus and treated with aerosolized ribavirin, experienced reduction in systemic illness and reduced virus shedding in nasal secretions with minimal adverse effects (McClung et al, 1983). However, other clinical trials have not been as encouraging (Cohen et al, 1976;Togo and McCracken, 1976;Magnussen et al, 1977;Smith et al, 1980;Stein et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a randomized, controlled study, 11 students infected with influenza B virus and treated with aerosolized ribavirin, experienced reduction in systemic illness and reduced virus shedding in nasal secretions with minimal adverse effects (McClung et al, 1983). However, other clinical trials have not been as encouraging (Cohen et al, 1976;Togo and McCracken, 1976;Magnussen et al, 1977;Smith et al, 1980;Stein et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…However, no specific therapy of proven value presently exists for treatment of serious influenza virus infections, including primary viral and mixed viral-bacterial pneumonias. Ribavirin (Virazole) has antiviral activity against influenza A and influenza B viruses in vitro (11,19) and in animal models of influenza, but clinical trials have found little evidence of therapeutic effectiveness (4,16,23,26). In an effort to develop alternative therapeutic approaches to single-drug therapy, the present study was undertaken to determine the antiviral activities of combinations of these drugs in vitro.…”
mentioning
confidence: 99%
“…Recently, it has been suggested that resistance to amantadine can be overcome by mixing amantadine with other amantadine derivatives that interfere with the ion channel function of M2 from amantadine-resistant viruses (Scholtissek et al, 1998). Ribavirin, a broad-spectrum antiviral agent Witkowski et al, 1972;Huffman et al, 1973;Oxford, 1975) has been considered for use against influenza A and B viruses, but the clinical trials of this compound have not been encouraging (Cohen et al, 1976;Togo & McCracken, 1976;Magnussen et al, 1977;Smith et al, 1980;Stein et al, 1987) and it has not been approved for the treatment of influenza virus infection.Historical accounts suggest that influenza has been around for centuries although influenza viruses have most likely been around for many thousands, perhaps millions, of years. Influenza viruses can cause highly contagious, febrile, acute respiratory illness in humans.…”
mentioning
confidence: 99%